Penerapan Layanan Bimbingan Kelompok untuk Mengurangi Gaya Hidup Hedonisme Remaja - Restiana Safitri; Winda Muliani; Putri Aulia Natasya (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of technology and globalization encourages hedonism and consumer behavior in adolescents, who often imitate celebrity lifestyles for recognition, risking eroding their identity. This study examines the effectiveness of group guidance in overcoming adolescent hedonism through qualitative literature studies. The results show that group guidance is effective in increasing self-awareness, the ability to manage finances, distinguish needs from wants, and build habits of saving and investing. Thus, group guidance is a strategic approach to forming wiser and more responsible adolescents.